Intraoperatively identified patellofemoral osteoarthritis: no significant impact on short-term outcomes of medial unicompartmental knee arthroplasty - Bei Li; Changyu Huang; Bingqian Zheng; Zida Huang; Xinyu Fang; Xiaoyong Wang; Wenming Zhang (BMC Musculoskeletal Disorders)
Abstract Background and objective The efficacy of medial unicompartmental knee arthroplasty (UKA) in patients with intraoperatively identified patellofemoral osteoarthritis (PFOA) has been a subject of debate. This retrospective study aimed to investigate the early outcomes of UKA in patients with varying intraoperative PFOA conditions and to explore the relationship between the location of PFOA and the position of the prosthesis post-UKA. Our aim was to determine whether the presence of PFOA affects the short-term success of medial UKA. Methods This single-center, retrospective study included patients who underwent UKA by a same surgical team from March 2021 to November 2022. Patients were categorized into normal, medial, middle, and lateral groups based on the intraoperative PFOA findings. A total of 103 patients were analyzed, with data collected on demographics, intraoperative details, and pre- and postoperative laboratory and imaging data. Patellofemoral joint cartilage damage was assessed using the Outerbridge classification. Postoperative patellofemoral joint function was evaluated using the Lonner score, Oxford Knee Score (OKS), and visual analog scale (VAS) for pain. Results Significant improvements were observed in postoperative Lonner pain scores, Lonner functional scores, OKS, and VAS compared to preoperative values for all groups (P < 0.05). Medial and middle PFOA identified intraoperatively did not affect the short-term efficacy of medial UKA. Although lateral PFOA had some impact on UKA efficacy, patients still experienced significant postoperative pain relief and functional improvement. Differences in the tibial component posterior slope angle (TCPSA) were noted among the groups, particularly between the medial and lateral groups (P < 0.05). Conclusion Intraoperatively identified medial and middle PFOA do not influence the short-term efficacy of medial UKA. Lateral PFOA has some impact on UKA outcomes, yet patients demonstrate significant improvements in postoperative pain and function. Intraoperative PFOA should not be considered an absolute contraindication for medial UKA. The study’s follow-up duration was relatively short, necessitating further research on the mid- to long-term effectiveness of UKA in patients with combined PFOA.